Grundtvigs forhold til Luther og den lutherske tradition - Grane, Leif (Grundtvig-studier, 1998)
Grundtvig's Relations with Luther and the Lutheran Tradition By Leif Grane Grundtvig’s relations with Luther and the Lutheran tradition are essential in nearly the whole of Grundtvig’s lifetime. The key position that he attributed to Luther in connection with his religious crisis 1810-11, remained with the Reformer until the very last, though there were changes on the way in his evaluation of the Reformation.The source material is overwhelming. It comprises all Grundtvig’s historical and church historical works, but also a large number of his theological writings, besides a number of his poems and hymns. Prior to Grundtvig’s lifelong occupation with Luther there had been a rejection of tradition as he had met with it in the Conservative supranaturalism. After the Romantic awakening at Egeløkke and the subsequent » Asarus« (the- ecstatic immersion in Nordic mythology), over the religious crisis 1810-1811, when Grundtvig thought he was »returning« to Luther, it was a different Luther from the one he had left a few years before. Though Grundtvig emphasizes the infallibility of the Bible, it is wrong to describe him as » Lutheran-Orthodox« in the traditional sense. In Grundtvig’s interpretation, Luther is above all the guarantee of the view of history he had acquired in his Romantic period, but given his own personal stamp, as it appeared in slightly different ways in the World Chronicles of 1812 and 1817. There already he turns against the theologization of the message of the Reformation that set in with the confessional writings. Ever since he maintained the view of the Reformation that he expounds in the two World Chronicles, though the evaluation of it changed somewhat, especially after 1825.The church view that Grundtvig presented for the first time in » Kirkens Gienmæle« (The Rejoinder of the Church), and which he explained in detail in » Om den sande Christendom« (About True Christianity) and » Om Christendommens Sandhed« (About the Truth of Christianity), was bound to lead to a conflict (as it did) with the Protestant » Scripturalism«, and thus to clarity about the disagreement with Luther. This conflict attained a greater degree of precision with the distinctions between church and state, and church and school, as they were presented in » Skal den lutherske Reformation virkelig fortsættes?« (Should the Lutheran Reformation Really Be Continued? 1830), but it was not really until the publication of the third part of » Haandbog I Verdens-Historien« (Handbook in World History) that the view of church history and of Luther’s place in it, inspired by the congregational letters in the Apocalypse, was presented, in order to be more closely developed, partly in poetical form in » Christenhedens Syvstjeme« (The Seven Star of Christendom), partly in lectures in » Kirke-Spejl« (Church Mirror).Grundtvig had to reject orthodoxy since the genuineness of Baptism and Eucharist depended on their originating from Christ Himself. Nothing of universal validity could therefore have come into existence in the 16th century.Thus the evaluation of Luther and Lutheranism must depend on how far Lutheranism corresponded to what all Christians have in common. Luther is praised for the discovery that only the Word and the Spirit must reign in the church. It is understandable therefore that Luther had to break down the false idea of the church that had prevailed since Cyprian, and Grundtvig remained unswervingly loyal to him. But he cannot avoid the question why Luther’s work crumbled after his death. The answer is that it crumbled because of » Scripturalism« which Grundtvig considers a spurious inheritance from Alexandrian theology. We must maintain Luther’s faith which centres on all that is fundamentally Christian, but not his theological method.Grundtvig believes that with his criticism of Luther he is really closer to him than those who are cringing admirers of him. Grundtvig confesses himself to having committed the mistake of confusing the Bible with Christianity, and he cannot exempt Luther from a great responsibility for this aberration. All the same, in Luther’s case the wrong Yet Luther was induced to want to make his own experiences universally valid since he did not understand that his own use of the Scriptures could not possibly be right for every man. Here Grundtvig is on the track of the individualism which to him is an inevitable consequence of Scripturalism: everybody reads as he knows best. It was not in school, but in church that he saw Luther’s great and imperishable achievement.So while Grundtvig cannot exempt Luther from some responsibility for an unfortunate development in the relation between church and school, he is very anxious to exempt him from any responsibility for the assumption of power in the church by the princes, which is due, in his opinion, to a conspiracy between the princes and the theologians with a view to tying the peoples to the symbolical books.In the development of Grundtvig’s view of church history it turns out that the interest in the national, cultural and civic significance of the Reformation has not decreased after he has given up fighting for a Christian culture. The Reformation must, as must church history on the whole, be seen in the context of the histories of the peoples. Therefore, if it is not to be pure witchcraft, it must have its foundation deep in the Middle Ages.Grundtvig points to what he calls »the new Christendom«: from the English and the Germans to the North. Viewed in that light, the Reformation is a struggle for a Christian life, a folkelig life of the people, and enlightenment.Though the 17th century wrenched all life out of what was bom in the 16th, and the 18th century abandoned both Christianity and folkelig life altogether, it was of great significance for culture and enlightenment that the people was made familiar with Luther’s catechism, Bible and hymn book. What was fundamentally Christian survived, while folkelig life lay dormant.The Reformation was unfinished, and its completion must wait until the end of time. But compulsion is approaching the end, and the force of the Reformation in relation to mother tongue and folkelig life manifests itself more strongly than ever before, Gmndtvig believes. What is fundamentally Christian in Luther must be maintained and carried onwards, while the Christian enlightenment, i.e. theology, depends on the time in question.Life is the same, but the light is historically determined. With this concept of freedom, which distinguishes between the faith in Christ as permanent and the freedom of the Holy Ghost that liberates us from being tied to the theology of the old, Gmndtvig may convincingly claim that it is he who – with his criticism - is loyal to Luther, i.e. to »the most excellent Father in Christ since the days of the Apostles«.